Determinants in sustaining a local information system in the Philippines the case of the Barangay Management System (BMIS) - Maneja, Charina P. (The Journal of Public Affairs and Development, 2012)
Information is important for the executive and legislative functions of local officials. The study determined the institutional and individual factors that contributed in sustaining a Barangay management Information System (BMIS). The study was done in five provinces covering 90 randomly selected continuing barangays and 68 randomly selected non-continuing barangays. Chi-square test of independence was used to determine factors associated with whether the bar angry will continue to sustain BMIS or not. Logistic regression analysis was also performed to determine factors that may influence barangay's decision to sustain BMIS. The identified significant individual factors that influenced the barangay's decision to sustain BMIS were the system's user-friendly features, ease in managing the BMIS software, and usefulness of data generated in performing the functions of the local government officials. The significant institutional factors that contributed to sustaining a Local Information System (LIS) were the active participation of the Barangay Council members in data management; the availability of budget and equipment; the presence of municipal and technical support from the municipalities and state universities and colleges; and the utilization of data in the submission of administrative reports, situational analysis for the preparation of plans, monitoring and targeting of beneficiaries; and the issuance of local ordinance for the adoption of LIS. Recommendations include strengthening the process of policy preparation at the local level; organization of the LIS team; creation of positions for Information or Investment Officers; crafting of ordinances to support the budgetary requirements; and establishment of partnerships between SUCs and the LGUs.